The Impact of Tourism on The Development of MSMEs in Tulang Bawang West District (Case Study of The Islamic Center Tourism Sector) - Anezza, Devis; Gunarto, Toto (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The Islamic Center is a tourist attraction in West Tulang Bawang Regency which has the advantage of being a religious tourist attraction. The aim of this research is to determine whether or not there are differences in income and turnover of MSMEs around the Islamic Center tourist attraction before and after the existence of this tourist attraction. This research uses the Stata analysis tool with descriptive statistical analysis methods proven by the Paired Samples Test, with a population of 109 MSMEs and the sample used is 52 MSMEs. The results of this research show that there are differences in income and turnover of MSMEs before and after the Islamic Center tourist attraction. This is indicated by the t value of -17.7844 and the p-value on the income variable is 0.000 so it is <0.05 and the t value is -21.4197 and the p-value on the turnover variable is 0.